(untitled) (Current Horticulture, 2024)
The ornamental flora of green spaces of the University of M’sila (Pole 2) includes 32 ornamental plants (tree, shrub and herbaceous), belonging to 22 botanical families and 29 genera. The greens contain 89 wild plants belonging to 29 families which find refuge at the edge and in these green spaces; of which the Asteraceae family is most abundant, in second place comes the Fabaceae and Poaceae families, then the Brassicaeae with and Euphorbiaceae on the other hand the Geraniaceae, the Plantaginaceae, the Polygonaceae are weakly represented. The chorological types of wild species show the dominance of the elements of the Mediterranean group over all other groups. The analysis of biological types of wild species reveals the dominance of therophytes over all biological types, followed by hemicryptophytes, geophytes and chamaephytes.